Red - Di Bonaventura, Lorenzo; Vahradian, Mark.; Schwentke, Robert, 1968-; Hoeber, Jon.; Hoeber, Erich; Willis, Bruce, 1955-; Mirren, Helen; Malkovich, John.; Parker, Mary-Louise.; Freeman, Morgan; Dreyfuss, Richard; McMahon, Julian, 1968-; et al. (Universal City, CA : Summit Entertainment, 2011)
Frank is a former black-ops CIA agent living a quiet life alone, until the day a hit squad shows up to kill him. With his identity compromised, Frank reassembles his old team; Joe, Marvin, and Victoria, and sets out to prove that they still have a few tricks up their sleeves. Stand back and watch the bullets fly in this explosive action- comedy.
DVD release of the 2010 motion picture.
Based on the graphic novel by Warren Ellis and Cully Hamner.
Special features: Deleted and extended scenes; Access: Red (cast insights); CIA exposed; audio commentary with retired CIA field officer Robert Baer.
Music, Christophe Beck ; editor, Thom Noble ; director of photography, Florian Ballhaus.
Bruce Willis, Helen Mirren, John Malkovich, Mary-Louise Parker, Morgan Freeman, Richard Dreyfuss, Julian McMahon, Brian Cox, Karl Urban, Ernest Borgnine.
MPAA rating: PG-13; for intense sequences of action violence and brief strong language.
Keywords: United States. -- Central Intelligence Agency -- Drama; Intelligence officers -- Drama; Attempted assassination -- Drama; Espa̕s -- Teatro; Fiction films; Action and adventure films; Comedy films; Film adaptations; Video recordings for the hearing impaired; Feature films; Feature films -- United States